Analysis of the Molecular Basis of Flowering Time Variation in Arabidopsis Accessions - Gazzani, Silvia (The American Society for Plant Biologists, 2003)
Allelic variation at the FRI (FRIGIDA) and FLC (FLOWERING LOCUS C) loci are major determinants of flowering time in Arabidopsis accessions. Dominant alleles of FRI confer a vernalization requirement causing plants to overwinter vegetatively. Many early flowering accessions carry loss-of-function fri alleles containing one of two deletions. However, some accessions categorized as early flowering types do not carry these deletion alleles. We have analyzed the molecular basis of earliness in five of these accessions: Cvi, Shakhdara, Wil-2, Kondara, and Kz-9. The Cvi FRI allele carries a number of nucleotide differences, one of which causes an in-frame stop codon in the first exon. The other four accessions contain nucleotide differences that only result in amino acid substitutions. Preliminary genetic analysis was consistent with Cvi carrying a nonfunctional FRI allele; Wil-2 carrying either a defective FRI or a dominant suppressor of FRI function; and Shakhdara, Kondara, and Kz-9 carrying a functional FRI allele with earliness being caused by allelic variation at other loci including FLC. Allelic variation at FLC was also investigated in a range of accessions. A novel nonautonomous Mutator-like transposon was found in the weak FLC allele in Landsberg erecta, positioned in the first intron, a region required for normal FLC regulation. This transposon was not present in FLC alleles of most other accessions including Shakhdara, Kondara, or Kz-9. Thus, variation in Arabidopsis flowering time has arisen through the generation of nonfunctional or weak FRI and FLC alleles.